2023
DOI: 10.3390/cancers15051532
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Crosstalk between Photodynamic Therapy and Immunotherapy in Breast Cancer

Abstract: Breast cancer (BC) is the world’s second most frequent malignancy and the leading cause of mortality among women. All in situ or invasive breast cancer derives from terminal tubulobular units; when the tumor is present only in the ducts or lobules in situ, it is called ductal carcinoma in situ (DCIS)/lobular carcinoma in situ (LCIS). The biggest risk factors are age, mutations in breast cancer genes 1 or 2 (BRCA1 or BRCA2), and dense breast tissue. Current treatments are associated with various side effects, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 154 publications
0
8
0
Order By: Relevance
“…Photodynamic therapy (PDT), which employs a photosensitizer to generate light-induced ROS, along with immunotherapy overcome the immune tolerance [ 311 ]. PDT-induced oxidative stress leads to calreticulin-mediated necrosis of tumor cells and secretes damage-associated molecular patterns (DAMPs) to cause antigen-presenting T cell activation [ 312 ].…”
Section: Therapeutic Strategies To Overcome Immunotherapy Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Photodynamic therapy (PDT), which employs a photosensitizer to generate light-induced ROS, along with immunotherapy overcome the immune tolerance [ 311 ]. PDT-induced oxidative stress leads to calreticulin-mediated necrosis of tumor cells and secretes damage-associated molecular patterns (DAMPs) to cause antigen-presenting T cell activation [ 312 ].…”
Section: Therapeutic Strategies To Overcome Immunotherapy Resistancementioning
confidence: 99%
“…PDT-induced phagocytosis in macrophages results in CD8 + T-cell activation [ 314 ]. PDT inhibits immunosuppressive TME along with its anti-tumor immune response [ 311 ]. It is used with immunomodulatory agents to prevent metastasis through improved CD8 + T cell stimulation [ 315 ].…”
Section: Therapeutic Strategies To Overcome Immunotherapy Resistancementioning
confidence: 99%
“…Breast cancer, in addition to being the second most commonly diagnosed cancer type among women, also ranks as the second leading cause of cancer-related deaths in women under the age of 40. , Despite the current breast cancer treatment methods, which include surgery, radiotherapy, chemotherapy, and targeted therapy, the frequency and significance of the disease necessitate the need for new treatments. , Photodynamic therapy (PDT) has emerged as one of the most important methods used in the treatment of cancer without the need for surgical intervention. Photodynamic therapy makes use of reactive oxygen species produced by the irradiation of photosensitizers (PSs). PSs, which take their place as light-absorbing species in PDT processes, are synthetic or natural chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…In another study from 2023 by Jin et al, [ 72 ] a number of studies have shown that immunotherapy combined with PDT enhances the results of anti-tumor drugs and reduces tumor immune escape. PDT combined with immunotherapy does not induce resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, blood vessel injury and tumor cells also attract macrophage infiltration, which regulates macrophage polarization and enhances macrophage phagocytosis of tumor cells. Natural killer cells (NK cells) and dendritic cells (DCs) activate adaptive immune cells, such as monocytes, cytotoxic T lymphocytes (CTLs), and B cells, to enhance the overall immune response by releasing cytokines [ 72 ].…”
Section: Introductionmentioning
confidence: 99%